ANALISIS PENGGUNAAN X POWER DAN VARIASI CAMPURAN BAHAN BAKAR PREMIUM – ETANOL TERHADAP KADAR GAS POLUTAN CO DAN HC PADA SEPEDA MOTOR SUPRA X 125 TAHUN 2009 - Suparyanto, Suparyanto (Jurnal Nosel, 2013)
ABSTRACT The purposes of this research are: (1)To know the use effect of X Power against levels of pollutant gases CO and HC on Honda Supra X 125 2009, (2)To know the effect of the addition of ethanol in premium on levels of pollutant gases CO and HC on Honda Supra X 125 2009, (3)To know the interactions effect using X Power and the addition of ethanol in premium on levels of pollutant gases CO and HC on Honda Supra X 125 2009. The research used experimental methods. Techniques of data analysis in this study using the descriptive data analysis graphically illustrates the results of research in the histogram or frequency polygon which connects between the variables. From the research, we can conclude that: (1)Using X Power 800 Gold on motorcycles especially Honda Supra X 125 2009 to reduce levels of pollutant gases CO and HC. (2)The addition of ethanol in premium fuel comparable straight with decreased levels of gas pollutant CO, the more the content of ethanol in premium fuel is getting smaller levels of CO, but inversely with decreased levels of gas pollutant HC, the more the content of ethanol in premium fuel higher levels of HC produced motorcycles especially Honda Supra X 125 2009. (3)Interaction between the best mixture of fuel premium- ethanol and the use of X Power 800 Gold in decreased levels of pollutant gases CO and HC are on mixture of fuel premium- ethanol 15% and the use of the X Power 800 Gold, which is 0.75% CO and 390 ppm HC, but the use this variation must attention the total cost.